(untitled) (PIONIR: JURNAL PENDIDIKAN, 2022)
The background of the problem based on an initial study conducted by a fifth grade mathematics teacher at MIS Nurul Hikmah Ujung Padang said that the students’ mathematics learning outcomes were quite good as seen from the student learning outcomes listed in the students’ final reports. From the perspective of learning theory that affects learning outcomes including interest and motivation, in this case there are still students who are lazy in doing homework (PR). Quantitative research is research using a quantitative research design aimed at capturing quantitative data in the form of numerical data using a validated instrument that reflects the dimensions and indicators of the variable and is distributed to a particular population or sample. Based on the method, this study uses the correlational method, which is a study to determine the relationship and level of relationship between two or more variables without any attempt to influence these variables so that there is no variable manipulation. This approach is used to describe the relationship between interest in learning mathematics and motivation to learn mathematics with students’ mathematics learning outcomes in class V MIS Nurul Hikmah Ujung Padang. Based on the results of research in this journal, the following conclusions can be drawn: There is a relationship between interest in learning and learning outcomes in mathematics. This can be seen based on data analysis using product moment correlation, obtained a price of 0.436> 0.329. With a significance value of 0.000 <0.05, it means that there is a significant relationship between learning interest and mathematics learning outcomes for fifth grade students at MIS Nurul Hikmah Ujung Padang. There is a relationship between learning motivation and mathematics learning outcomes. This can be seen based on the calculations performed using the product moment, namely (0.486> 0.329). With a significance value of 0.008 < 0.005, it means that there is a significant relationship between learning motivation and mathematics learning outcomes for fifth grade students at MIS Nurul Hikmah Ujung Padang. There is a significant relationship between interest in learning and learning motivation with learning outcomes in mathematics.